The politics of personalised medicine : - Hedgecoe, Adam (Cambridge University Press, 2004)
This book applies a social science perspective to an examination of issues that arise in clinical practice as a result of drug development linked to genetic testing. These include the social context within which new drugs undergo trials and the related attitudes and expectations of clinicians and patients. Two case studies illustrate the arguments--one on aspects of Alzheimer's disease, and the other on the drug Herceptin which is used in the treatment of breast cancer